Brain-Derived Neurotrophic Factor Precursor in the Hippocampus Regulates Both Depressive and Anxiety-Like Behaviors in Rats - Zhong, Feng; Liu, Lei; Wei, Jia-Li; Hu, Zhao-Lan; Li, Li; Wang, Shuang; Xu, Jun-Mei; Zhou, Xin-Fu; Li, Chang-Qi; Yang, Zhao-Yun; Dai, Ru-Ping (Frontiers in Psychiatry, 2019)
Depression and anxiety are two affective disorders that greatly threaten the mental health of a large population worldwide. Previous studies have shown that brain-derived neurotrophic factor precursor (proBDNF) is involved in the development of depression. However, it is still elusive whether proBDNF is involved in anxiety, and if so, which brain regions of proBDNF regulate these two affective disorders. The present study aims to investigate the role of proBDNF in the hippocampus in the development of depression and anxiety. Rat models of an anxiety-like phenotype and depression-like phenotype were established by complete Freund's adjuvant intra-plantar injection and chronic restraint stress, respectively. Both rat models developed anxiety-like behaviors as determined by the open field test and elevated plus maze test. However, only rats with depression-like phenotype displayed the lower sucrose consumption in the sucrose preference test and a longer immobility time in the forced swimming test. Sholl analysis showed that the dendritic arborization of granule cells in the hippocampus was decreased in rats with depression-like phenotype but was not changed in rats with anxiety-like phenotype. In addition, synaptophysin was downregulated in the rats with depression-like phenotype but upregulated in the rats with anxiety-like phenotype. In both models, proBDNF was greatly increased in the hippocampus. Intra-hippocampal injection anti-proBDNF antibody greatly ameliorated the anxiety-like and depressive behaviors in the rats. These findings suggest that despite some behavioral and morphological differences between depression and anxiety, hippocampal proBDNF is a common mediator to regulate these two mental disorders.